Pengaruh Latihan Fleksi William (Stretching) Terhadap Tingkat Nyeri Punggung Bawah Pada Lansia Di Posyandu Lansia Rw 2 Desa Kedungkandang Malang - Hamidatus Daris Sa'adah, - (2008)
The elderly lessen their physical activity after pension, although daily activity need many muscle. Even elders with chronic health disorder or just suffering symptom of aging process admit do physical exercise in hip. Low back pain is feeling of area pain in bone lumbal sakral and sakroiliakal. Purpose of this study was explaining influence flexsi william ( Stretching) exercise to degradation of low back pain for elderly in RW2 in ofKedungkandang Malan g. Design was Pre Experimental by using " pre group one test post test design". Number of sampel 20 respondent, taken according inclusion criteria. The sampling used Purposive Sampling. Independent Variable was fleksi william (Stretching) exercise and dependent variable was low back pain for elerly. Data collection used interview. Data analyze used Wilcoxon Signed Rank Test Result showed that flexi william ( Stretching) exercise to decrease low back pain for elderly with p= 0,000 and signifikans value :S 0,05 meaning Hl accepted to mean the existence of influence of practice of flexi William (Stretching) to decrease of low back pain fur elder. Giving of practice of fleksi william (Stretching) can decrease low back pain in for elder because of flexi william (Stretching) exercise assist elderly flexi muscle effect of muscle spasme so that can decrease low back pain. For research is hereinafter expected to use responder which is more within old ones to get result of accurate